Cultivating Teachers When the School Doors Are Shut: Two Teacher-Educators Reflect on Supervision, Instruction, Change and Opportunity During the Covid-19 Pandemic - Loose, Crystal C.; Ryan, Michael G. (Frontiers in Education, 2020)
Seven weeks into our Spring 2020 semester, the Covid-19 pandemic was wreaking havoc on the world. The pandemic caused immediate shutdowns to schools and universities fundamentally changing how we plan for, teach, guide, and work with students. This paper explores how two first-year Assistant Professors navigated the challenges we faced and the learning opportunities we embraced while continuing our work as teacher educators amid a pandemic-induced shutdown. We employed collective self-study to examine our experiences while transitioning to remote learning with pre-service teachers using Moore’s (2012, 1993, 1989) transactional distance theory as an analytical framework to review our work as teachers in an online setting. We found that educators need to be open to continuous enhancements of instructional practices, there is a need to develop ways to equalize positions between the instructor and students, and we need to be conscious of opportunities students have to demonstrate creativity in their work. As part of this review, we developed and used a Four R’s Professional Inquiry Model (Recognition, Reflection, Reaction, Results) based on Moore’s work to help make meaning of our findings and recommendations for other practitioners.